When AI meets influencers: Role of AI-powered instagram influencers driving consumers’ purchase intentions: An integration of SMIV & SOR framework - Rohit Dhiman; Narender Singh Bhati (Journal of Open Innovation: Technology, Market and Complexity)
Artificial intelligence (AI) has become a game changer for Instagram influencers. AI assists influencers in refining their attributes by providing insights into the latest trends and enables influencers to create tailored content that engages audiences at a profound level. Despite such advancements, consumers fall into the trap of trusting the wrong influencer, posing a significant challenge for them to identify and trust the right influencer. Therefore, this study examines the Impact of AI-powered Instagram influencer attributes on consumers’ purchase intentions by integrating the Social Media Influencer Value (SMIV) and Stimulus-Organism-Response (SOR) models with 391 responses collected using purposive and snowball sampling. The empirical data were analyzed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) using Smart-PLS 4.0. The findings highlighted that both Interaction and Trustworthiness were the most significant factors impacting Brand Awareness and Trust in Branded Posts, which in turn affect Purchase Intention (PI). This study will benefit brands, business firms, Instagram influencers, and most importantly the consumers in determining the most essential AI-powered Instagram influencer’s attributes that drive PI. While the output of this study is confined to Instagram and primarily focused on northern India, the recommendations hold significance for other social media platforms and are applicable worldwide.